Visualizing translation dynamics at atomic detail inside a bacterial cell - Xue, Liang; Lenz, Swantje; Zimmermann-Kogadeeva, Maria; Tegunov, Dimitry; Cramer, Patrick; Bork, Peer; Rappsilber, Juri; Mahamid, Julia (Nature, 2022)
Translation is the fundamental process of protein synthesis and is catalysed by the ribosome in all living cells1. Here we use advances in cryo-electron tomography and sub-tomogram analysis2,3 to visualize the structural dynamics of translation inside the bacterium Mycoplasma pneumoniae.